Entrapment of a Dormia Basket in the Cystic Duct: Case Report - Dario Pariani; Giorgio Zetti; Ferdinando Cortese (Case Reports in Surgery)
Nowadays endoscopic treatment of common bile duct stones is considered the treatment of choice for all common bile duct stones. Although this procedure is related to a good success rate, in rare cases serious complications can happen, especially if you use a Dormia basket. Here we describe the clinical case of a patient affected by hepatolithiasis, cholelithiasis, and common bile duct lithiasis with entrapment of a Dormia basket in the cystic duct. It was necessary to perform a surgical choledochotomy to deal with this rare complication.